Pathological problems - Case study of the Antônio Papini Public School in João Monlevade, Brazil (Research, Society and Development, 2019)
The phases that encompass the construction lifecycle consist of project, execution and maintenance. A good and detailed project, a quality execution and a scheduled maintenance can contribute positively to accomplishment and extension of this cycle. This article presents a case study of construction pathologies in the public school Antônio Papini in João Monlevade, Brazil. The identified pathologies are fissure opening in the masonry walls and in the floor system in classrooms and library of the school. Symptoms, origins, mechanisms, causes were analyzed and a best conduct for repair was provided. The methodology of the study was based on classification systems proposed in the literature, conduct definitions, search of architectonic project, site surveys, photographic reports and graphic reproduction for compare the circumstances and elucidate the decision-making. The results obtained are discussed and presented. The relevance of this article is studying the pathologies and its interferences in the global performance of the building.